SISTEM INFORMASI PEMESANAN BARANG PADA BENGKEL TAWAKKAL JAYA BERBASIS WEB - Rusdiana, Lili; Sugianoor, Dhehen; Rosmiati, Rosmiati (LPPM STMIK STIKOM Indonesia, 2018)
The Tawakal Jaya workshop previously used paper for data recording, goods ordering transaction, and promotion. This results in the manual system less efficient in saving time. Therefore it is necessary to design and development of Information Systems Ordering Goods Based Website at Workshop